A Literature Review: Challenges of Internationalization in Small and Micro Enterprises Medium (SMEs) - Nurul Khaerani, Siti; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (Publisher Cv. Inara, 2023)
This article aims to find out the challenges faced by SMES in entering international markets. The methodology in writing this article is literature review. And limited to articles related to field studies. The search results found several articles with the specified keywords. Some of the challenges faced by SMEs in entering international markets in several countries such as Fiji, Nigeria, India, Nepal, Bangladesh, Finland and Sweden in entering international markets include access, both access to limited knowledge of international markets, access to finance, geographical conditions, and several other challenges. It is hoped that this article will provide benefits for finding solutions in facing the challenges of SMEs in facing the international market.